Physical Well-Being of Children and Adolescents during the SARS-CoV-2 Pandemic: Findings from the "Come te la Passi?" Cross Sectional Survey in Bologna, Italy - Aurelia Salussolia; Jacopo Lenzi; Marco Montalti; Flavia Rallo; Martina Paternò; Marta Agosta; Davide Resi; Michela Stillo; Federica Guaraldi; Davide Gori; Laura Dallolio; Alice Masini (MDPI AG, 2022)
Background: The COVID-19 had a strong impact on the physical and general well-being of the youngest. In Italy, citizens were forced to change their habits, especially during the national lockdown, causing increased levels of sedentary and unhealthy behaviors. "Come te la passi?" was a cross-sectional study aimed at investigating changes in the physical activity levels (PA) and well-being of children and adolescents in the City of Bologna. Methods: An anonymous survey was administered to parents/guardians of children and adolescents aged 6-18 years. Results: 1134 questionnaires were collected during June 2021; 457 (40.3%) were females, and the mean age was 13.0 ± 3.4 years. Regarding the general well-being perception, 61.3% of the participants reported concerns about the future, 46.3% reported sleep difficulties, and 72.8% reported experiencing attention difficulty, with higher percentages among adolescents. Considering the PA frequency, an overall reduction was found, with the percentage of those who rarely did PA and those who frequently did PA both increasing. No gender differences were found. Conclusions: Our findings suggest that the current pandemic has strongly impacted the well-being of children and adolescents. It appears to have primarily affected adolescents, with a significant reduction in PA levels, even after the end of the national lockdown.